Properties of zeolite-based geopolymer foam reinforced nanocellulose prepared in low alkaline media - Tay, Chai Hua (2024)
The growing interest in geopolymer foam, driven by its exceptional properties and environmental benefits, presents promising prospects for diverse industrial applications. However, its reliance on highly concentrated alkaline solutions and fresh water poses significant limitations. Concentrated alkaline solutions are expensive, low in supply, and corrosive, while fresh water is becoming scarce globally. This study developed geopolymer foams using low molarity alkaline solutions and seawater to address these issues. The geopolymer consisted of aluminosilicate zeolite, a mixture of Potassium Silicate (KSil), below 2M Potassium Hydroxide (KOH), Potassium Chloride (KCl), and seawater as the alkaline solution, with Sodium Lauryl Ether Sulphate (SLES) and Benzalkonium Chloride (BAC) as surfactants to stabilize the foam produced by Hydrogen Peroxide (H2O2). Nanocellulose (NC) was used as reinforcement. Geopolymerisation validation revealed successful depolymerization, reticulation, networking, and solidification of aluminosilicates, indicating that low molarity alkaline solution and seawater can effectively produce geopolymers. Response Surface Methodology (RSM) was used to statistically analyze the impact of each material on properties such as density, porosity, water absorption, and compressive strength. All four models displayed high R² values of more than 0.85, indicating that the chosen factors (SW/KSil, KOH/KCl, SLES/BAC, and H2O2/NC) effectively explain the variability in the tested properties. Optimization yielded a density of 1.691 g/cm³, porosity of 52.86%, water absorption of 43.106%, and compressive strength of 0.677 MPa, each with an average error below 15%. This study is the first to report on low molarity alkaline solution and seawater-based geopolymer foam, highlighting its potential as an eco-friendly alternative for various applications.